Mechanism of Electronic Charging of Coal Mine Dust - Cheng Xue-Zhen; Cao Mao-Yong; Wei A-Ying; Li Ji-Ming; Laxmisha Rai (Institute of Advanced Engineering and Science, 2013)
The electronic charging of mine dust can cause coal-dust explosion and increase the risk of pneumoconiosis, so it is necessary to take more attention to the study of its electronic charging properties. The mechanism of electronic charging of coal mine dust was investigated in this paper. It was found that the formation and polarity of dust are determined by the energy band structure and of the two contacting sides; then a mathematical model of work function is established in mesoscopic level. The experiments conclude that the work function decreases with the particle size for the dust with same properties, moreover large particles are positively charged and small particles are negatively charged. Finally, the experimental verification of the main particles charged model drive unipolar and bipolar charged modes and confirm the correctness of microstructure and mesoscopic analyses, which furthermore lay the foundation for further research. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3237